LC-ESI-QTOF-MS/MS characterization of phenolic compounds from Pyracantha coccinea M.Roem. and their antioxidant capacity - Sharifi-Rad, Javad; Song, Shengnan; Ali, Akhtar; Subbiah, Vigasini; Taheri, Yasaman; Suleria, Hafiz A.R. (Cellular and Molecular Biology, 2021)
Pyracantha coccinea M.Roem. is considered as an important medicinal plant contributing remarkably to health and medicinal benefits. This is attributed to the presence of abundant polyphenols with powerful antioxidant properties. However, little research has been studied on the comprehensive identification and characterization of the phenolic compounds in areal parts of P. coccinea.  This study aimed to investigate, characterize, and quantify the phenolic profiles of P. coccinea through liquid chromatography electrospray ionization quadrupole time-of-flight mass spectrometry (LC-ESI-QTOF-MS/MS) and high-performance liquid chromatography-photodiode array (HPLC-PDA. Further, it showed a significantly higher value in total phenolic content (TPC) than that of total flavonoids (TFC) and tannins (TTC). As for antioxidant capacities, P. coccinea presented the highest activity in ABTS (7.12 ± 0.25 mg AAE/g dw) compared with DPPH, FRAP, and TAC assays. The LC-ESI-QTOF-MS/MS analysis detected 28 phenolic compounds, including phenolic acids (12), flavonoids (13), other polyphenols (2), and lignans (1) in P. coccinea samples. The results from HPLC–PDA indicated the chlorogenic acid (11.49 ± 1.89 mg/g) was the most abundant phenolic acid, while kaempferol (14.67 ± 2.17 mg/g) was the predominant flavonoid in P. coccinea. This research confirms the benefits of the P. coccinea plant as a potential source of natural antioxidants for the food and pharmaceutical industries.